2018
DOI: 10.1051/0004-6361/201832680
|View full text |Cite
|
Sign up to set email alerts
|

The feedback of an HC HII region on its parental molecular core

Abstract: Context. G24.78+0.08 is a well known high-mass star-forming region, where several molecular cores harboring OB young stellar objects are found inside a clump of size ≈1 pc. This article focuses on the most prominent of these cores, A1, where an intense hypercompact (HC) HII region has been discovered by previous observations. Aims. Our aim is to determine the physical conditions and the kinematics of core A1, and study the interaction of the HII region with the parental molecular core. Methods. We combine ALMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Along the outflow direction, the centroid velocity linearly increases with distance at velocities V lsr +33 km s −1 or V lsr +88 km s −1 (marked by the red triangles). The fitted velocity gradients are 4.9 ± 0.19 km s −1 mas −1 (0.58 ± 0.02 km s −1 au −1 ) for the blue-shifted emissions and 2.6 ± 0.09 km s −1 mas −1 (0.31 ± 0.01 km s −1 au −1 ) for the red-shifted emissions, which are among the highest seen in ionized flows around forming massive stars (e.g., Moscadelli et al 2018). Note that the two high-velocity Gaussian components in the H30α spectrum (Figure 2c) have central velocities of V lsr = +25 and +80 km s −1 , which are close to the velocities where the centroid pattern changes from rotation to outflow.…”
Section: Dynamics Of the Ionized Gasmentioning
confidence: 96%
“…Along the outflow direction, the centroid velocity linearly increases with distance at velocities V lsr +33 km s −1 or V lsr +88 km s −1 (marked by the red triangles). The fitted velocity gradients are 4.9 ± 0.19 km s −1 mas −1 (0.58 ± 0.02 km s −1 au −1 ) for the blue-shifted emissions and 2.6 ± 0.09 km s −1 mas −1 (0.31 ± 0.01 km s −1 au −1 ) for the red-shifted emissions, which are among the highest seen in ionized flows around forming massive stars (e.g., Moscadelli et al 2018). Note that the two high-velocity Gaussian components in the H30α spectrum (Figure 2c) have central velocities of V lsr = +25 and +80 km s −1 , which are close to the velocities where the centroid pattern changes from rotation to outflow.…”
Section: Dynamics Of the Ionized Gasmentioning
confidence: 96%
“…We originally targeted G17.64 along with five other luminous O-type (proto)stars 1 with ALMA and found mixed evidence for discs around the various targets using the typical CH 3 CN tracer (Cesaroni et al 2017). Our detailed investigations to-date of two of these six sources, G31.41+0.31 and G24.78+0.08 (Beltrán et al 2018;Moscadelli et al 2018), found clear velocity gradients in the CH 3 CN 12-11 line transitions. In G31.41+0.31, the gradient is indicative of rotational spin-up and infall towards the two central cores, whereas for G24.78+0.08, it is due to wind and outflow feedback from the O-star at the centre of an HCHII region.…”
Section: Introductionmentioning
confidence: 93%
“…There are several sources associated with this star-forming region but we focus on the hot molecular cores A1 and A2. G24 A1 contains a hypercompact HII region (∼1000 au) which has been determined to be expanding through methanol, water maser, and recombination line observations (Beltrán et al 2007;Moscadelli et al 2018). G345.49+1.47 (hereafter G345, also known as IRAS 16562-3959), shown in the bottom panel of Figure 1, is located at a distance of 2.4 kpc with a bolometric luminosity of 1.5 ×10 5 L .…”
Section: Source Samplementioning
confidence: 99%
“…For full details on observations and continuum subtraction see Cesaroni et al (2017). The continuum intensity for subsources showing H30α emission were corrected for free-free emission with direct measurements for G17 from Maud et al (2018), G24 A1 from Moscadelli et al (2018), and calculated for G345 using the spectral index fit from Guzmán et al (2016).…”
Section: Observationsmentioning
confidence: 99%